A Reformist, a Diplomat, and a Benevolent Merchant: Hājī Mīrzā Sayyīd Muhammad-Taqī Shīrāzī (Afnān), the Shīrāzī Trading House and the Propagation of the Babi-Baha ʾi Faith - Shahvar, Soli (Journal of the economic and social history of the Orient, 2020)
Abstract The aim of this paper is to offer a glimpse into the Baha ʾi mercantile community in Iran during the second half of the nineteenth century and its reformist and modernist attitudes through the accounts of one of its leading merchants, Hājī Mīrzā Sayyīd Muhammad-Taqī Shīrāzī (Afnān).